A role for the MRN complex in ATR activation via TOPBP1 recruitment - Duursma, Anja M; Driscoll, Robert; Elias, Josh E; Cimprich, Karlene A (Molecular cell, 2013)
The MRN (MRE11-RAD50-NBS1) complex has been implicated in many aspects of the DNA damage response. It has key roles in sensing and processing DNA double-strand breaks, as well as in activation of ATM (ataxia telangiectasia mutated). We reveal a function for MRN in ATR (ATM- and RAD3-related) activation by using defined ATR-activating DNA structures in Xenopus egg extracts. Strikingly, we demonstrate that MRN is required for recruitment of TOPBP1 to an ATR-activating structure that contains a single-stranded DNA (ssDNA) and a double-stranded DNA (dsDNA) junction and that this recruitment is necessary for phosphorylation of CHK1. We also show that the 911 (RAD9-RAD1-HUS1) complex is not required for TOPBP1 recruitment but is essential for TOPBP1 function. Thus, whereas MRN is required for TOPBP1 recruitment at an ssDNA-to-dsDNA junction, 911 is required for TOPBP1 "activation." These findings provide molecular insights into how ATR is activated.